Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1983
DOI: 10.1007/bf02330060
|View full text |Cite
|
Sign up to set email alerts
|

Further studies on dynamic crack branching

Abstract: The newly derived dynamic crack branching criterion is verified by dynamic photoelastic analysis of dynamic crack branchings in thin polycarbonate, single edged crack tension specimens. Successful crack branching was observed in four specimens and unsuccessful branchings in another. Crack branching consistently occurred when the necessary condition of KIb = 3.3 MPa miind the sufficient condition of r o = rc = 0.7 m were satisfied simultaneously.In the unsuccessful branching test the necessary conditon was not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
16
0

Year Published

1985
1985
2006
2006

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 11 publications
3
16
0
Order By: Relevance
“…The dependence 7(V) takes place only in the regime of controlled fracture for dT/dV > 0; in this case, the dependences 7(u) and 7(V) are similar (they differ only in the scale on the velocity axis). The results agree with the data of [10,23], but only qualitatively agree with the data of [17]. The appreciable increase in 7 at V > 100 m/sec and Kla at v > 104 sec -1 is caused by the local heating of the material at the crack tip due to transition to adiabatic conditions and "unfreezing" of the SHV relaxation process.…”
Section: P(t) = Ese(t)supporting
confidence: 79%
“…The dependence 7(V) takes place only in the regime of controlled fracture for dT/dV > 0; in this case, the dependences 7(u) and 7(V) are similar (they differ only in the scale on the velocity axis). The results agree with the data of [10,23], but only qualitatively agree with the data of [17]. The appreciable increase in 7 at V > 100 m/sec and Kla at v > 104 sec -1 is caused by the local heating of the material at the crack tip due to transition to adiabatic conditions and "unfreezing" of the SHV relaxation process.…”
Section: P(t) = Ese(t)supporting
confidence: 79%
“…This concept was applied to dynamic crack curving by Ramulu and Kobayashi [8]. In accordance with previous findings, Ramulu et al [9] observed that successful branching always took place at a constant value of K I , which was therefore cited as a necessary condition for branching to occur. Under these conditions, multiple off-axis secondary cracks were generated and the dynamic curving criterion provided a sufficient condition for these secondary cracks to kink simultaneously.…”
Section: Introductionmentioning
confidence: 55%
“…Earlier work by Kalthoff [10] pointed out that attraction or repulsion between the two branches is controlled by the ratio K II /K I . Ramulu et al [9] observed that the photoelastic patterns of running branched cracks initially showed strong mixed mode effects but the mode II effect weakened as the cracks propagated, and eventually approached K II = 0.…”
Section: Introductionmentioning
confidence: 99%
“…Crack branching in brittle materials has been a subject of theoretical [1][2][3][4] and experimental [5][6][7][8][9][10][11][12][13][14][15][16][17][18] studies. In particular, a criterion which controls the initiation of crack branching has drawn the attention of many researchers.…”
Section: Introductionmentioning
confidence: 99%
“…Hence different propositions have been proposed as to the role of the high crack velocity. Several researchers suggested that Kd should play a dominating role while high crack velocity should be a necessary but not a sufficient condition for the branching [6][7][8][9]14]. Recently a review of crack branching has been given by Ramulu and Kobayashi [18].…”
Section: Introductionmentioning
confidence: 99%